2021
DOI: 10.18094/josc.871290
|View full text |Cite
|
Sign up to set email alerts
|

Sınıf Öğretmenlerinin Dijital Okuryazarlık Düzeylerinin İncelenmesi

Abstract: Dünyada olduğu gibi ülkemizde de hız kesmeden gelişen teknoloji çalışmaları eğitimde de kendini göstermektedir. COVİD-19 pandemi nedeniyle eğitimin ulusal çapta zorunlu olarak uzaktan yapılmasıyla eğitimde teknoloji kullanımı zorunlu hale gelmiştir. Bu süreç dijital yerli olarak adlandırılan günümüz öğrencilerine sürece uyum sağlamasının kendini geliştiren ve teknolojiyi derslerde kullanabilen öğretmenler ile mümkün olduğunu göstermiştir. Bu durumda öğretmenlerin dijital okuryazarlık becerileri uzaktan eğitimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 22 publications
0
13
0
6
Order By: Relevance
“…Accordingly, primary school teachers are at the moderate level in instructional technologies such as using animation tools, spreadsheet programs, in-class measurement, and evaluation technologies; at a very good level in information and communication aspects such as instant messaging technologies, sharing information obtained with digital technologies, shopping over the internet; and at a very good level in technical aspects such as transferring files between digital technologies, using a USB memory or external disk, and making a webcam connection. Studies reporting similar results in the literature revealed that teachers' digital literacy levels are at moderate level (Aksoy et al, 2021;Arslan, 2019;Ata & Yıldırım, 2019;Can et al, 2020;Erol and Aydın, 2021;Ocak & Karakuş, 2019;Özerbaş & Öçal, 2019;Özoğlu, 2019;Üstündağ et al, 2017;Velez et al, 2017); and at very sufficient levels (Korkmaz, 2020;Öztürk and Budak, 2019). This difference can be affiliated with the time teachers spend on the Internet and computers, or their interest in digital tools and equipment.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Accordingly, primary school teachers are at the moderate level in instructional technologies such as using animation tools, spreadsheet programs, in-class measurement, and evaluation technologies; at a very good level in information and communication aspects such as instant messaging technologies, sharing information obtained with digital technologies, shopping over the internet; and at a very good level in technical aspects such as transferring files between digital technologies, using a USB memory or external disk, and making a webcam connection. Studies reporting similar results in the literature revealed that teachers' digital literacy levels are at moderate level (Aksoy et al, 2021;Arslan, 2019;Ata & Yıldırım, 2019;Can et al, 2020;Erol and Aydın, 2021;Ocak & Karakuş, 2019;Özerbaş & Öçal, 2019;Özoğlu, 2019;Üstündağ et al, 2017;Velez et al, 2017); and at very sufficient levels (Korkmaz, 2020;Öztürk and Budak, 2019). This difference can be affiliated with the time teachers spend on the Internet and computers, or their interest in digital tools and equipment.…”
Section: Discussionmentioning
confidence: 62%
“…Accordingly, it can be concluded that primary school teachers with less seniority have higher digital literacy. Research in the literature are in parallel with these results (Aksoy et al, 2021;Erol & Aydın, 2021;Korkmaz, 2020;Özerbaş & Öçal, 2019). It can be concluded that the seniority of teachers adversely affects their digital literacy.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Bu teknolojilerin eğitime entegrasyonu ve yeni öğrenme gereksinimlerinin karşılanarak eğitimde kalitenin arttırılabilmesinde yeni nesil öğrencilerin dijital okuryazarlık becerilerine sahip olmalarının gerekliliği ve bu becerilerinin gelişimini sağlamada öğretmenlere yeni roller yüklenmiştir (MEB, 2020). Öğretmenler ve öğretmen adaylarıyla ilgili yapılan çalışmalarda dijital okuryazarlık seviyelerinin genellikle orta ve yüksek düzeyde olmalarına karşın (Çetin, 2016;Sarıkaya, 2019;Karakuş ve Ocak, 2019;Tekin ve Polat, 2017;Kozan ve Özek, 2019;Yazar ve Keskin, 2016;Yontar, 2019) bu becerilerini öğrenme-öğretme ortamlarına entegre edebilmelerinde yeterli seviyede olmadıkları yönündedir (Aksoy, Karabay ve Aksoy, 2021;Güneş ve Buluç, 2017). Bu teknolojilerin entegre edilmesinin önemli paydaşlarından biri olan web pedagojik içerik bilgisi açısından da sonuçlar benzerdir.…”
Section: Değişkenler Arasındaki İlişkiunclassified